Pelatihan Peningkatan Kompetensi Bimbingan dan Konseling Untuk Guru SD di Kabupaten Bengkalis - Rusandi, M. Arli; Yakub, Elni; Umari, Tri; Rahmansyah, Dedi; Syamsurizal, Muhammad; Darwis, Sajid Royhan; Salsabila, Ghina; Fauzi, Yoga Alwan; Nurzuraidah, Nurzuraidah; Khairunnisa, Nada; Putri, Navisa Syakila; Sudjono, Kirana Putri Livasya (Journal of Community Engagement Research for Sustainability, 2023)
Currently, the implementation of Guidance and Counseling in Elementary Schools is still not optimal, as evidenced by the absence of formation of Guidance and Counseling Teachers in Elementary Schools. The subject teacher or homeroom teacher is the spearhead for Guidance and Counseling activities in elementary schools. This community service activity aims to improve the competence of elementary school teachers in Bengkalis Regency so that they have broad insight regarding the implementation of guidance and counseling in elementary schools in order to improve the quality of guidance and counseling services so that the development of students in elementary schools becomes optimal in terms of aspects of the Physical-Aspects. Motor, cognitive, social, emotional, moral, and religious. The method used is brain storming, training-simulation and question and answer discussion. The evaluation was carried out by distributing a questionnaire on understanding and measuring the results of chronological assignments. 100% implementation of activities with full attendance of participants for 2 days of training. The increase in the competence of elementary school teachers after being given guidance and counseling training is 80%.